STUDIES ON THE EFFICIENCY OF COWDUNG COMPOST AS FOOD PRODUCER IN CARP (CYPRINUS CARPIO) CULTURE - Jamil, Khalid; Sultana, Razia; Shah, Abbas; Hong, Lin (Biological Sciences - PJSIR, 2001)
Studies were undertaken to determine the efficiency of composted bio waste in carp (Cyprinus carpio) culture for a period of 180 days. Growth offish was measured in terms of weight. The main increase in weight per fish at the end of the culture period was recorded in control, treated group A (compost) and treated group B (compost and feed) respectively. Statistically significant differences were found between the weight of experimental fish under control, treatment A and B groups. In this experiment none of the values recorded for water chemistry was beyond the tolerance of fish. It is concluded that with bio waste favourable change could be achieved in fish culture, which would help to reduce the running cost of the fish culture.